PENINGKATAN KEMAMPUAN NEMBANG DURMA LARAS SLENDRO PADA PEMBELAJARAN SENI SUARA JAWA - kandarsih, upik (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2016)
This study is a class action aims to improve students skills in nembang Durma in class VI using props saron. This research was conducted with 2 cycles. Each cycle consists of four phases: planning, action, observation, and reflection. Data collection techniques in this study is documentation, observations, and tests. Technical analysis of the data used to determine the advantages and disadvantages in the performance of teachers and students during the learning process. The subjects of this study are six graders State Kedungmutih Wedung District of Demak district. Implementation for two months from August to September 2015. The results of this classroom action research shows that there is significant increase in the ability of students. The results mean nembang test students on the initial conditions 37.5 and 37.5% level of completeness. In the first cycle the average value of 71.5 completeness rate of 50%. In the second cycle mean value 77.0 and 83.3% level of completeness. Based on the above, it can be concluded that by using props saron in sound art learning Java, can improve students skills in nembang Durma Laras Slendro.